Temperature investigation of infrared-to-visible frequency upconversion in erbium-doped tellurite glasses excited at 1540 nm - Vermelho, MVD; Gouveia-Neto, A. S.; Amorim, H. T.; Cassanjes, F. C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2003)
Temperature investigation of infrared-to-visible frequency upconversion in erbium-doped tellurite glasses excited by CW laser radiation at 1540 nm and under cryogenic temperatures is reported. Intense upconversion emission signals around 530, 550 and 660 nm corresponding to the H-2(11/2), S-4(3/2), and F-4(9/2) transitions to the I-4(15/2) ground state were generated and studied as a function of the laser intensity and temperature. The upconversion excitation mechanism of the Er3+ ions emitting energy levels was accomplished via stepwise multiphoton absorption. The green upconversion luminescence exhibited a fivefold intensity enhancement when the temperature of the sample was varied in the range between 5 and 300 K. A maximum green upconversion intensity was attained around 120 K and a steady decreasing behavior for higher temperatures up to 300 K was observed. A model based upon conventional rate equations was used to model the observed temperature evolution of the upconversion luminescence. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: upconversion; glass; rare earth